Spolupráce středních odborných škol a zaměstnavatelů - Hloušková, Lenka; Kryštof, David; Michek, Stanislav (Masarykova univerzita, 2023)
Cílem příspěvku je představit dílčí výsledky kvantitativního výzkumného šetření, které mapuje charakter spolupráce středních odborných škol (včetně učilišť) a zaměstnavatelů pohledem vedení škol a učitelů. Charakter spolupráce je zásadní nejen pro rozvoj středních odborných škol, ale ovlivňuje i procesy učení se na pracovišti a vzdělávací výsledky žáků. Konkrétně se v příspěvku zaměřujeme na rozmanitost a míru spolupráce a výsledky diskutujeme ve vztahu k tzv. politice založené na důkazech.

The aim of this paper is to introduce the quantitative research survey results that focused on the cooperation between secondary technical schools and employers from the perspective of school leaders and teachers. The character of the employer engagement is key not only for school development, it also impacts workplace learning and learning outcomes of students. We deal with the diversity and extent of the cooperation and we discuss the partial results in the context of evidence-based policy.
Collaboration between secondary technical schools and employers
Keywords: střední odborné školy; zaměstnavatelé; spolupráce; secondary technical schools; employer engagement; cooperation